2022
DOI: 10.1002/hbm.25885
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal white matter microstructural changes in pediatric mild traumatic brain injury: AnA‐CAPstudy

Abstract: In the largest sample studied to date, white matter microstructural trajectories and their relation to persistent symptoms were examined after pediatric mild traumatic brain injury (mTBI). This prospective, longitudinal cohort study recruited children aged 8-16.99 years with mTBI or mild orthopedic injury (OI) from five pediatric emergency [Correction added on 04 May 2022, after first online publication: Quynh Doan's affiliation is updated and subsequent affiliations were re-numbered.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…The children with mTBI and OI did not differ in any global network metrics before or after each harmonization approach. This was expected given that DTI and NODDI indices of white matter microstructure did not differ between groups previously in this sample (18,32,35), and other pediatric samples at similar time points (52). Another study compared a subset of this sample (children recruited at the Calgary site) to typically developing children and also did not find global or regional (nodal) network differences between mTBI and mild OI groups post-acutely, but did find an effect of injury more generally relative to typical development (18).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The children with mTBI and OI did not differ in any global network metrics before or after each harmonization approach. This was expected given that DTI and NODDI indices of white matter microstructure did not differ between groups previously in this sample (18,32,35), and other pediatric samples at similar time points (52). Another study compared a subset of this sample (children recruited at the Calgary site) to typically developing children and also did not find global or regional (nodal) network differences between mTBI and mild OI groups post-acutely, but did find an effect of injury more generally relative to typical development (18).…”
Section: Discussionsupporting
confidence: 54%
“…All participants provided written informed assent and parents/guardians provided written informed consent (22). This study examined data from the MRI scans collected during the post-acute visit, as previously described (32,35).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, although the current study exclusively focused on GM changes postinjury, several recent studies have also observed white matter pathology post-pmTBI in large samples that also persist multiple months postinjury. 45,47 Thus, future studies that examine pathology from a multimodal perspective are needed, as well as the potential relationship between injury biomarkers and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%